Customer awareness of buying green product: a study at Komtar JBCC / Nor Rasyidah Mohd Tahir and Mohammad Suhairi Mohammad - Mohd Tahir, Nor Rasyidah; Mohammad, Mohammad Suhairi (Faculty of Business and Management, 2015)
The main purpose of this study is to determine the level of customer awareness about buying green product. There are four factors that lead to buying green product which are consumers’ environmental concerns, awareness of green product, awareness of price and awareness of brand image. The researchers want to identify the most influential factor of purchasing green product. To examine the factors affecting the purchasing green product, a questionnaire was distributed to a random size using convenient sampling technique of 150 customers out of 5000 customers per month that comes to Komtar Jbcc. The SPSS software package system was used to analyze the data and then proceed with regression analysis and Pearson’s correlation to test the hypotheses. The findings show that brand image and price significantly influences customers from purchasing the green products. Finally, the researcher had provides some recommendations for the marketers or entrepreneurs aspects and customers aspects in term of increase the awareness of buying green product in future.